Starling house eaudiobook - Harrow, Alix E. (Macmillan Audio, 2023)
NEW YORK TIMES BESTSELLER | A REESE'S BOOK CLUB PICK "This book has everything you could possibly want this fall...a cursed town, a haunted house, a vivid & eerie setting—plus, characters willing to risk everything." —Reese Witherspoon (Reese's Book Club October '23 Pick) Starling House is a gorgeous, modern gothic fantasy from the New York Times bestselling author of The Ten Thousand Doors of January. I dream sometimes about a house I've never seen.... Opal is a lot of things—orphan, high school dropout, full-time cynic and part-time cashier—but above all, she's determined to find a better life for her younger brother Jasper. One that gets them out of Eden, Kentucky, a town remarkable for only two things: bad luck and E. Starling, the reclusive nineteenth century author of The Underland , who disappeared over a hundred years ago. All she left behind were dark rumors—and her home. Everyone agrees that it's best to ignore the uncanny mansion and its misanthropic heir, Arthur. Almost everyone, anyway. I should be scared, but in the dream I don't hesitate. Opal has been obsessed with The Underland since she was a child. When she gets the chance to step inside Starling House—and make some extra cash for her brother's escape fund—she can't resist. But sinister forces are digging deeper into the buried secrets of Starling House, and Arthur's own nightmares have become far too real. As Eden itself seems to be drowning in its own ghosts, Opal realizes that she might finally have found a reason to stick around. In my dream, I'm home. And now she'll have to fight. Welcome to Starling House: enter, if you dare. A Book of the Month Club Pick An October 2023 Indie Next Pick A LibraryReads October 2023 Hall of Fame Pick Apple, Best Books of October EW.com, Fall Book Must Reads 2023 Washington Post , Noteworthy Books for October Paste Magazine , The Must-Read Fantasy Books of Fall 2023 PopSugar Best New Fantasy Books of 2023 BookPage , Most Anticipated Books of Fall 2023 Observer , Must-Read Books of Fall 2023 Polygon , 12 Best New SFF for the Fall LitHub , October's Best Sci-Fi and Fantasy Books Bookish, October's Most-Anticipated Books Gizmodo , October's Huge List of New Sci-Fi, Fantasy, and Horror Books A Macmillan Audio production from Tor Books.